A dinuclear oxo-bridged molybdenum(VI) complex containing a bidentate pyrazolylpyridine ligand: Structure, characterization and catalytic performance for olefin epoxidation - Amarante, Tatiana R.
The oxo-bridged dinuclear complex [Mo2O4(mu(2)-O)Cl-2(pypzEA)(2)] (2) (pypzEA = ethyl[3-(pyridin-2-yl)-1H-pyrazol-1-yl]acetate) was obtained upon the treatment of [MoO2Cl2(pypzEA)] (1) with ethanol. The molecular structure of 2 consists of two highly distorted MoClN2O3 octahedra sharing a corner oxygen atom, with a Mo - O -Mo \"kink\" angle of 163.2(2)degrees and a Mo center dot center dot center dot Mo separation of 3.7029(7) angstrom. Catalytic results with 2 for the epoxidation of cis-cyclooctene using tert-butylhydroperoxide as oxidant compare favorably with those reported for related oxomolybdenum(VI) complexes. The reaction is homogeneous in nature, and a fraction of 2 dissolves and is converted to other types of soluble active species, one of which was isolated and identified as the oxodiperoxo complex [MoO(O-2)(2)(pypzEA)] (3). (C) 2013 Elsevier B.V. All rights reserved.